EMG-EMG coherence during voluntary control of human standing tasks: a systematic scoping review - Yamanaka, Eiji; Horiuchi, Yuki; Nojima, Ippei (Frontiers in Neuroscience, 2023)
Background: Intra- or inter-muscular (EMG-EMG) coherence is a simple and non-invasive method for estimating central nervous system control during human standing tasks. Although this research area has developed, no systematic literature review has been conducted. Objectives: We aimed to map the current literature on EMG-EMG coherence during various standing tasks to identify the research gaps and summarize previous studies comparing EMG-EMG coherence between healthy young and elderly adults. Methods: Electronic databases (PubMed, Cochrane Library, and CINAHL) were searched for articles published from inception to December 2021. We incorporated studies that analyzed EMG-EMG coherence of the postural muscles in various standing tasks. Results: Finally, 25 articles fulfilled the inclusion criteria and involved 509 participants. Most participants were healthy young adults, while only one study included participants with medical conditions. There was some evidence that EMG-EMG coherence could identify differences in standing control between healthy young and elderly adults, although the methodology was highly heterogeneous. Conclusion: The present review indicates that EMG-EMG coherence may help elucidate changes in standing control with age. In future studies, this method should be used in participants with central nervous system disorders to understand better the characteristics of standing balance disabilities.